Civil society and government - Rosenblum, Nancy L. (Nancy Lipton), 1947-; Post, Robert, 1947- (Ethikon series in comparative ethics., 2002)
Civil Society and Government brings together an unprecedented array of political, ethical, and religious perspectives to shed light on the complex and much-debated relationship between civil society and the state. Some argue that civil society is a bulwark against government; others see it as an indispensable support for government. Civil society has been portrayed both as a independent of the state and as dependent upon it. This book reveals the extraordinary diversity of views on the subject by examining how civil society has been treated in classical liberalism, liberal egalitarianism, critical theory, feminism, natural law, Christianity, Judaism, Islam, and Confucianism. The volume draws on the work of eminent scholars to address six questions: In terms of function and consequences, does it matter where the line is drawn between civil society and the state? What is the relationship of civil society to the state? In what contexts and under what conditions should government interact with individuals directly or instead indirectly through communal associations? What are the prerogatives and duties of citizenship, and what is the role of civil society in forming good citizens? How should a society handle the conflicts that sometimes arise between the demands of citizenship and those of membership in the non-governmental associations of civil society? A theoretical introduction by the editors--political theorist Nancy Rosenblum and legal scholar Robert Post--and a conclusion by religious ethicist Richard Miller, tie the book together. In addition to Rosenblum, the contributors are Kenneth Baynes, David Biale, John Coleman, Farhad Kazemi, John Kelsay, William Galston, Will Kymlicka, Tom Palmer, Fred Miller, Susan Moller Okin, Peter Nosco, Henry Rosemont, Steven Scalet, David Schmidtz, William Sullivan, Max Stackhouse, Stephen White, and Noam Zohar.